2014
DOI: 10.1186/1471-2474-15-126
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of endopeptidase and angiotensin-converting enzyme lead to an amplification of the morphological changes and an upregulation of the substance P system in a muscle overuse model

Abstract: BackgroundWe have previously observed, in studies on an experimental overuse model, that the tachykinin system may be involved in the processes of muscle inflammation (myositis) and other muscle tissue alterations. To further evaluate the significance of tachykinins in these processes, we have used inhibitors of neutral endopeptidase (NEP) and angiotensin-converting enzyme (ACE), substances which are known to terminate the activity of various endogenously produced substances, including tachykinins.MethodsInjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In rabbit studies, inhibition of ACE revealed [in combination with neutral endopeptidase inhibitor] elevated muscle damage in a muscle overuse model induced by electrical stimulation every second day with four sessions in total (Song et al 2014 ), which is in line with the human findings of Yamin et al ( 2007 ). The muscle damage was accompanied by increased tachykinin, substance P and its preferred receptor neurokinin-1 receptor expression, which suggests that the tachykinin family may play a role in the inflammatory processes and pain (Song et al 2014 ; Dousset et al 2007 ). Substance P is widely expressed in human cells and tissues of the peripheral and central nervous systems but it is also found in extra neuronal cells and innervated tissues.…”
Section: Additional Gene Polymorphisms Associated With Exercise-inducsupporting
confidence: 60%
“…In rabbit studies, inhibition of ACE revealed [in combination with neutral endopeptidase inhibitor] elevated muscle damage in a muscle overuse model induced by electrical stimulation every second day with four sessions in total (Song et al 2014 ), which is in line with the human findings of Yamin et al ( 2007 ). The muscle damage was accompanied by increased tachykinin, substance P and its preferred receptor neurokinin-1 receptor expression, which suggests that the tachykinin family may play a role in the inflammatory processes and pain (Song et al 2014 ; Dousset et al 2007 ). Substance P is widely expressed in human cells and tissues of the peripheral and central nervous systems but it is also found in extra neuronal cells and innervated tissues.…”
Section: Additional Gene Polymorphisms Associated With Exercise-inducsupporting
confidence: 60%
“…NEP and ACE inhibitors administered intravenously along with SP, was found to cause muscle inflammation in rabbit after one week while only minimal changes were observed in the control group. Levels of SP and NK-1R was high in the inflamed muscles [39] .…”
Section: Introductionmentioning
confidence: 86%
“…Substance P-NK-1R signaling has been implicated as inducing hypercellularity and collagen production in fibrotic tendinopathies and myositis, and has been proposed as a therapeutic target for their treatment, 32,37,38 although to our knowledge, these are first studies of this kind in an animal model of overuse-induced musculoskeletal disorders. We sought here to determine if Substance P-NK-1R signaling contributes to the early progression of sensorimotor declines and fibrogenic responses in multiple tissue types involved in performing a HRHF task using a specific NK1R antagonist (L-732,138) delivered intraperitoneally in the final 2 weeks of a 3-week task.…”
Section: Discussionmentioning
confidence: 99%
“…Substance P and NK1R increase in tendons and muscles with overuse, [32][33][34][35] and the Substance P-NK1R pathway has been implicated as an inducer of collagen production of over-use fibrotic tendinopathies. 32,37 The NK1R has been proposed as a therapeutic target for their treatment, 32,37,38 although this hypothesis has yet to be tested in vivo.…”
Section: Introductionmentioning
confidence: 99%